Anaesthetic management of a young primigravida with 8 months amenorrhea, rheumatic heart disease, hypothyroidism and met-hemoglobinimea schedule for cesarean section - Katyal, Misha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
A young patient, primigravida with rheumatic heart disease, hypothyroidism and met-hemoglobinemia had central and peripheral cyanosis was scheduled for caesarean section under general anesthesia in two days. Author managed met-hemoglobinemia with ascorbic acid keeping methylene blue as standby. Haemoglobin saturation was 89% at room air and 92% with supplemental oxygen. Initial met-haemoglobin levels were 31.54% (normal values <1%). After optimizing thyroid and RHD status (moderate MR and mild MS), she was given tablet ascorbic acid 2 gram thrice a day with methylene blue as standby. Conventional balanced general anesthesia technique was used and she was followed up in postoperative period with ICU care. A healthy live female baby was extracted and mother had stable vital parameters. Postoperative treatment with ascorbic acid was continued. Repeated methaemoglobin levels showed a drop from preoperative value of 31.54% to 11.39% by 3rd postoperative day and 8.05% at the end of 1st week. At the time of discharge, she did not have any cyanosis. Ascorbic acid is a good alternative drug with limited experience in met-hemoglobinemia. Author present a case of a met-hemoglobinemia treated with ascorbic acid successfully to emphasize the use of ascorbic acid as an alternative method without any adverse effects.